Young‐onset frontotemporal dementia in a homozygous tau R406W mutation carrier. Issue 12 (12th November 2015) - Ng, Adeline S. L.; Sias, Ana C.; Pressman, Peter S.; Fong, Jamie C.; Karydas, Anna M.; Zanto, Theodore P.; De May, Mary; Coppola, Giovanni; Geschwind, Daniel H.; Miller, Bruce L.; Lee, Suzee E.
Abstract: Microtubule‐associated protein tau mutations result in 10–20% of cases of genetic frontotemporal lobar degeneration. Tau mutation carriers typically develop behavioral variant frontotemporal dementia with or without parkinsonism. Unlike most frontotemporal dementia gene mutations, heterozygous R406W tau mutation carriers most often develop clinical Alzheimer's disease. We report a homozygous tau R406W mutation carrier with behavioral variant frontotemporal dementia who developed symptoms 20 years before mean family symptom onset. Voxel‐based morphometry showed frontoinsular, frontal, and mesial temporal cortical atrophy. Homozygous tau R406W mutations appear to accelerate symptom onset and drive a behavioral variant frontotemporal dementia syndrome.